(Study of Tertiary Irrigation Canals In The Sei Beras Sekata Village Sei Krio Sunggal, Deli Serdang District - Sri Amelia Susan Ginting; Sumono Sumono; Ainun Rohana (Universitas Sumatera Utara, 2013)
In the distribution of irrigation water through a soil tertiary canal, there can be a great loss of water, sedimentation and canal scoured if not well designed. This research was aimed to review, to calculate the waterloss and efficiency as well as to designing a good canal dimensions of tertiary canals to prevent scour and sedimentation at 2 tertiary canals in the Sei Beras Sekata village Sei Krio Sunggal, Deli Serdang district. The results showed that sedimentation occurred in both tertiary canals, so that redesign of the dimensions on the both canals was needed. Efficiency at the same distance (30m) in the canal 1 was 79,42 % and canal 2 was 91,72 %. The best tertiary canal dimensions for canal 1 was the combination 0,02% slope, the channel width (B) was 0,62 m and the depth of water (D) was 0,31 m and for canal 2 was the combination 0,02% slope, the canal width (B) was 0,58 m and the depth of water (D) was 0,29 m. Key Word: Tertiary Canal, Waterloss, Conveyance Efficiency and Canal Dimensions